Penyelesaian Persamaan Poisson 2D Dengan Menggunakan Metode Gauss-Seidel dan Conjugate Gradien - Dewi Erla Mahmudah; Muhammad Zidny Naf'an (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2017)
In this paper we focus on solution of 2D Poisson equation numerically. 2D Poisson equation is a partial differential equation of second order elliptical type. This equation is a particular form or non-homogeneous form of the Laplace equation. The solution of 2D Poisson equation is performed numerically using Gauss Seidel method and Conjugate Gradient method. The result is the value using Gauss Seidel method and Conjugate Gradient method is same. But, consider the iteration process, the convergence of the value is reached faster using Conjugate Gradient method.